(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To study the etiology, various mechanisms of injury and outcome of orthopedic trauma in elderly patients presenting to the Emergency Department of a tertiary care hospital. Methods: The data was prospectively collected over a period of 1 year (Jan 2015-Dec 2015) at the Jinnah Postgraduate Medical Centre’s orthopaedic bay in the Emergency Department. 692 elderly trauma-patients above 65 years were included. The doctors on duty filled out a simple questionnaire for every patient that presented with orthopedic injury. Statistical analysis was done using SPSS version 20. Results: Falls on the same plane were the most common cause of injury at 67.1% (n=464), while road traffic accidents were the second most common accounting for 22.55% (n= 156), and alarmingly third came gunshot injuries at 2.3 % (n=16). The most common site of injury due to falls was the lower limb at 43.9% (n=304) while the upper limb was 23.1% (n =160). Of the fall injuries, 81.9% (n=464) had a fall on the same plane while 18.1% (n=84) had a fall from 10 feet or higher. Conclusion: The percentage of elderly patients amongst the general population is increasing day by day and so is the risk for trauma. Aggressive management to counteract this increase in geriatric trauma is required, along with sensitivity to issues such as elder abuse. An emphasis on nationwide policies and state run programs for elder citizens regarding healthcare and primary disease prevention as well as their rehabilitation will serve to reduce the burden on an already poverty stricken nation.